Pelatihan dan Pemanfaatan E-Commerce sebagai Media Pemasaran Produk UMKM di Kecamatan Cikarang Pusat - Meidiana Putri Alyssa; Etty Zuliawati Zed; Jasmine Nanda Shabirah; Ayu Ainunisa (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The implementation of this community service involves one MSME, namely 'Mask and Furniture Wholesale Shop'. Located in Jayamukti Village, Central Cikarang District, Bekasi Regency or about 4.0 km from Pelita Bangsa University. MSMEs wholesale masks and furniture play a strategic role in meeting community needs, especially during the pandemic and changes in people's lifestyles that lead to online shopping. This service aims to examine the effect of training and e-commerce utilization in improving the competitiveness and operational efficiency of wholesale stores in this sector. Through training that focuses on the use of e-commerce platforms and internet-based marketing strategies, it is hoped that this training can evaluate the impact of digital transformation on the business growth of mask and furniture wholesale stores. The method used is a qualitative method, namely through a case study approach and in-depth interviews with MSME players, with the aim of analyzing the effectiveness of training that focuses on the use of ecommerce platforms and online marketing strategies. The results of the service showed that ecommerce training improved the ability of MSMEs to access a wider market, optimize business management, and increase sales. In addition, MSME players also face challenges such as technology adaptation and logistics management. This study provides recommendations on the importance of continuous training, technological infrastructure support, and collaboration between the government and e-commerce platforms to maximize the potential of wholesale MSMEs in the digital era.. .